A Unique Autophosphorylation Site on Tie2/Tek Mediates Dok-R Phosphotyrosine Binding Domain Binding and Function - Jones, Nina (American Society for Microbiology, 2003)
Tie2/Tek is an endothelial cell receptor tyrosine kinase that induces signal transduction pathways involved in cell migration upon angiopoietin-1 (Ang1) stimulation. To address the importance of the various tyrosine residues of Tie2 in signal transduction, we generated a series of Tie2 mutants and examined their signaling properties. Using this approach in conjunction with a phosphorylation state-specific antibody, we identified tyrosine residue 1106 on Tie2 as an Ang1-dependent autophosphorylation site that mediates binding and phosphorylation of the downstream-of-kinase-related (Dok-R) docking protein. This tyrosine residue is contained within a unique interaction motif for the phosphotyrosine binding domain of Dok-R, and the pleckstrin homology domain of Dok-R further contributes to Tie2 binding in a phosphatidylinositol 3′-kinase-dependent manner. Introduction of a Tie2 mutant lacking tyrosine residue 1106 into endothelial cells interferes with Dok-R phosphorylation in response to Ang1. Furthermore, this mutant is unable to restore the migration potential of endothelial cells derived from mice lacking Tie2. Together, these findings demonstrate that tyrosine residue 1106 on Tie2 is critical for coupling downstream cell migration signal transduction pathways with Ang1 stimulation in endothelial cells.